Malignant melanoma: Statistical study at the Hospital de Clínicas - D'Auria, Agustín; Borges, Freddy; De Los Santos, Julio; Falconi, Luis; Mate, Miguel; Priario, Julio César (Cirugía del Uruguay, 1978)
111 patients with Maiignant Melanoma, treated by the Oncological Unit of the Surgical Service "B" of the Hospital de Clínicas of Montevideo between 1964 and 1972 were studied. 61 were female and 50 male. Melanomas were rnost frequently seen among the 61-70 years old group. The most common place where melanoma has been found has been the leg ( 43 patients) especially in females ( 28 patients). Primary lesion without lymph nade metastases has been found in 53 patlents. Treatment of the primary was performed in 54 % of the cases outside of the Hospital. The rest have been submitted to wide excision of the primary, usually ( 3/51) without fascial resection. A lyrnph node regional dissection was performed in 40 cases, 27 as a therapeutical procedure and 13 as an elective one. Total percentage of patients with 5 year survival has been 29.4 %, Best results were obtained in fernale patients, with primary lesion placed in the leg, without regional lymph nades.